Gestão Departamental em Cirurgia 20 Anos de Experiência - Costa, Moreira da (2010)
The author presents a series of thoughts and reflections about a new kind of Departmental organization, that was put in practice at Hospital de Santo António – Porto, 20 years ago. The rationale and advantages to be expected from such a new form of organizations, then pioneer in this Country, together with the enumeration of its national and foreign precursors is presented. Also its implication of the functional Status of Emergency and Accident Departments and its impact on training of Residents is analysed. A few reflections on the advantages that can be expected in the fields of increased proficiency in the execution of the most complex and rare surgical techniques, as well, as the potential benefits both for the performing surgeon and the patient are taken into consideration. The author concludes by suggesting a few possible corrections than can improve de global work-out of the model, as well as its applicability to the various kinds of institutions present in the field. Keywords: Departmental organization, Post Graduate teaching